2022
DOI: 10.1101/2022.09.12.22279750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Debiasing and Educational Interventions in Medical Diagnosis: A Systematic Review

Abstract: Background: The prevalence of cognitive bias and its contribution to diagnostic errors has been documented in recent research. Debiasing interventions or educational initiatives are key in reducing the effects and prevalence of cognitive biases, contributing to the prevention of diagnostic errors. The objectives of this review were to 1) characterize common debiasing strategies implemented to reduce diagnosis-related cognitive biases, 2) report the cognitive biases targeted, and 3) determine the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Mamede et al ’s study aligns with other investigations which find that steering the brain toward the analytical mode has limited prospects for improving diagnosis 2–5. Vignette studies lack ecological validity (eg, text cases cannot capture the context of a patient encounter),6 but their design allows for the interrogation of concepts that inform medical education based on sound logic but limited evidence.…”
Section: Analysing the Analytical Modementioning
confidence: 59%
“…Mamede et al ’s study aligns with other investigations which find that steering the brain toward the analytical mode has limited prospects for improving diagnosis 2–5. Vignette studies lack ecological validity (eg, text cases cannot capture the context of a patient encounter),6 but their design allows for the interrogation of concepts that inform medical education based on sound logic but limited evidence.…”
Section: Analysing the Analytical Modementioning
confidence: 59%
“…Unfortunately, this awareness of, and discomfort with, self-identified bias may not necessarily lead to better advocacy actions by the learner. While Sukhera et al identified a promising acceptability among providers to address their own biases about their patients [28], it can be extremely difficult for individuals to identify and address biases [29][30][31][32]. By definition, our own biases are always, to some extent, unknown to us [30].…”
Section: Discussionmentioning
confidence: 99%
“…Despite strategies for teaching and employing cognitive debiasing techniques, debate has existed about the extent to which such approaches are effective[ 45 ]. Several recent systematic and scoping reviews of debiasing interventions show promise for improvement of diagnostic accuracy, but the results of studies are heterogeneous[ 46 - 48 ]. Importantly, none of the studies examined decision-making in a clinical setting, and no studies reported long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%